Long‐term outcomes of index cryoballoon ablation or point‐by‐point radiofrequency ablation in patients with atrial fibrillation and systolic heart failure. (10th February 2021) - Prabhu, S.; Ahluwalia, N.; Tyebally, S. M.; Dennis, A. S. C.; Malomo, S. O.; Abiodun, A. T.; Tyrlis, A.; Dhillon, G.; Segan, L.; Graham, A.; Honarbakhsh, S.; Sawhney, V.; et al.
Abstract: Catheter ablation is an established effective approach for the treatment of atrial fibrillation (AF) in patients with heart failure, however, the role of cryoablation in this setting is unclear. Procedural success and left ventricular systolic dysfunction (LVEF) improvement in patients with LVEF ≤ 45% undergoing index catheter ablation with cryoablation were evaluated. Freedom from AF recurrence was seen in 43% rising to 59% following repeat procedure. There were significant improvements in LVEF and functional status at long‐term follow‐up. Results were comparable to a contemporaneous cohort of heart failure patients undergoing index ablation with radiofrequency ablation. Cryoablation is an effective first‐line AF ablation approach in the setting of heart failure.